2018
DOI: 10.1038/s41467-018-02876-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological methane production under putative Enceladus-like conditions

Abstract: The detection of silica-rich dust particles, as an indication for ongoing hydrothermal activity, and the presence of water and organic molecules in the plume of Enceladus, have made Saturn’s icy moon a hot spot in the search for potential extraterrestrial life. Methanogenic archaea are among the organisms that could potentially thrive under the predicted conditions on Enceladus, considering that both molecular hydrogen (H2) and methane (CH4) have been detected in the plume. Here we show that a methanogenic arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 55 publications
3
103
1
5
Order By: Relevance
“…2018 described an alternative way to indirectly quantify CH 4 productivity by the turnover rate [h −1 ] (Equation ). This parameter, while neglecting biomass formation, is described by the difference in pressure before and after incubation Δ p , the maximum theoretical pressure difference due to stoichiometry Δ p max , and the time period Δ t of incubation . turnoverrateh1=ΔpΔpmaxΔt…”
Section: Methodsmentioning
confidence: 99%
“…2018 described an alternative way to indirectly quantify CH 4 productivity by the turnover rate [h −1 ] (Equation ). This parameter, while neglecting biomass formation, is described by the difference in pressure before and after incubation Δ p , the maximum theoretical pressure difference due to stoichiometry Δ p max , and the time period Δ t of incubation . turnoverrateh1=ΔpΔpmaxΔt…”
Section: Methodsmentioning
confidence: 99%
“…Different classification schemes have been published to describe planetary bodies based on their 'habitability' (e.g., Lammer et al, 2009;Noack et al, 2016;Schulze-Makuch et al, 2017). Several studies have also demonstrated the growth of microorganisms under lab-simulated planetary conditions, including Mars-like (Fajardo-Cavazos et al, 2018;Nicholson et al, 2013;Schuerger and Nicholson, 2016) and Enceladus-like (Taubner et al, 2018) conditions. In this context, defining the boundary limits of life on Earth is a crucial step in identifying the conditions likely to originate or support life on other planetary bodies.…”
Section: Can Life Originate Evolve or Survive On Other Planetary Bomentioning
confidence: 99%
“…It should be noted that we are restricting our attention here to surface dwelling life on planets orbiting their star. Thus, life in subsurface oceans and/or on icy moons like Enceladus [41], or even more exotic types of life (e.g., [42,43]), are not considered. It is our plan to consider these alternative environments in future work.…”
Section: Number Of Habitable Planets Per Star N Ementioning
confidence: 99%